Probing CO2 Reduction Pathways for Copper Catalysis Using an Ionic Liquid as a Chemical Trapping Agent. Issue 41 (3rd September 2020) - Zhang, Gui‐Rong; Straub, Sascha‐Dominic; Shen, Liu‐Liu; Hermans, Yannick; Schmatz, Patrick; Reichert, Andreas M.; Hofmann, Jan P.; Katsounaros, Ioannis; Etzold, Bastian J. M.
Abstract: The key to fully leveraging the potential of the electrochemical CO2 reduction reaction (CO2RR) to achieve a sustainable solar‐power‐based economy is the development of high‐performance electrocatalysts. The development process relies heavily on trial and error methods due to poor mechanistic understanding of the reaction. Demonstrated here is that ionic liquids (ILs) can be employed as a chemical trapping agent to probe CO2RR mechanistic pathways. This method is implemented by introducing a small amount of an IL ([BMIm][NTf2 ]) to a copper foam catalyst, on which a wide range of CO2RR products, including formate, CO, alcohols, and hydrocarbons, can be produced. The IL can selectively suppress the formation of ethylene, ethanol and n‐propanol while having little impact on others. Thus, reaction networks leading to various products can be disentangled. The results shed new light on the mechanistic understanding of the CO2RR, and provide guidelines for modulating the CO2RR properties. Chemical trapping using an IL adds to the toolbox to deduce the mechanistic understanding of electrocatalysis and could be applied to other reactions as well. Abstract : The presence of a small amount of ionic liquid significantly alters the product spectrum of CO2 reduction over a Cu catalyst. The ionic liquid acts as a chemical trapping agent, selectively suppressing the formation of C2+ products that involve carbene as a key intermediate. The response in product distribution to ionic liquid modification offers a new way to disentangle the complex reaction network of CO2 reduction by Cu catalysts.